Development and assessment of in vitro tumour models for anti-cancer drug testing - Liu, X (2011)
The study of the development of anti-cancer drugs and preclinical efficacy tests has until today encountered a major problem identified as lack of reliable in vitro tumour models which are able to reflect in vivo tumour conditions. These models provide a clear basis for understanding tumour development processes, assisting in the selection of agents from various chemicals and testing the efficacy of drugs. There are two important characteristics for an in vitro tumour model, i.e. tumour-like structure of cell aggregates, and the in vivo-like culture microenvironment. To meet these two requirements, an in vitro perfusion based three-dimensional tumour model was developed for the three dimensional culture of cancer cells and related anti-cancer drugs tests. In order to assess this model, DLD1 and NCI/ADR cells were cultured in four different models and compared their proliferation rate, cell viability, micro tumour formation and drug responses. In addition, the comparison of static and perfusion culture were done on monolayer and in 3D also. The cells in perfusion culture showed higher proliferation rates and significantly, higher cell viabilities after a 6-day culture compared to statically cultured cells, especially for the cells in the 3D culture. Microtumours (MTs) were formed from this model, which showed significant tumour-like morphological characteristics, a denser and highly stable structure, a higher cell viability, and varied drug responses compared with spheroids. The inhibition effect of paclitaxel and cisplatin, two common type anti-cancer drugs, were tested and a comparative study was carried out using conventional two-dimensional (2D) static culture, spheroids, and the developed 3D MTs model, as well as real human tumour tissues. The results showed that the cells in 2D culture were most greatly inhibited while human tumours showed the lowest drug responses. The efficacy of anti-cancer drugs, tested in conventional 2D static culture, was greatly amplified. Besides, the response of MTs to agents was much closer to that of human tumours, when the values of spheroids are relatively closer to the cells in 2D culture. It is further supported that MTs have more tumour-like characteristics than spheroids. When compared, the inhibition to proliferation of cells in static and perfusion culture showed significantly different drug responses except for the cells on the monolayer. The shown difference between static and perfusion culture can be due to the different culture environment, and further related to the different action mechanisms of anti-cancer agents. The perfusion culture provides a more homogenous and more physiological microenvironment for the in vitro tumour growth, and in vitro perfused 3D cancer model, developed in this thesis, proved valuable for the study of in vitro cancer and related anti-cancer drug tests.